Systematic review of clinical practice guidelines on the management of community acquired pneumonia in children. (June 2022) - Chee, Elyssa; Huang, Kathryn; Haggie, Stuart; Britton, Philip N.
Abstract: Childhood community acquired pneumonia (CAP) is the leading cause of mortality in children under 5 years worldwide. Clinical practice guidelines (CPGs) may be limited by method of development, scope of recommendations and the quality of supporting evidence. This study systematically identified, appraised and compared the recommendations of CPGs for the management of paediatric CAP using the AGREE II tool. The systematic review yielded 1409 non-duplicate results, of which 14 CPGs were appraised. Four of the fourteen CPGs were deemed high quality. Most CPGs were considered low-medium quality with 'rigour of development' and 'applicability' the weakest domains. These areas should be considered in deriving CPGs in the future. Recommendations were generally similar across all guidelines; however, there was notable heterogeneity in three areas. This suggests the need for further evidence to guide management decisions on oxygen saturation thresholds for admission, the utility of investigations such as acute phase reactants, and the duration of antibiotic therapy.